Low-wage employment - Schnabel, Claus (Forschungsinstitut zur Zukunft der Arbeit GmbH (IZA), 2021)
Low-wage employment has become an important feature of the labor market and a controversial topic for debate in many countries. How to interpret the prominence of low-paid jobs and whether they are beneficial to workers or society is still an open question. The answer depends on whether low-paid jobs are largely transitory and serve as stepping stones to higher-paid employment, whether they become persistent, or whether they result in repeated unemployment. The empirical evidence is mixed, pointing to both stepping-stone effects and
10.15185/izawol.276.v2
Keywords: Graue Literatur; low-wage employment; wages; stepping stone; state dependence